1991
DOI: 10.1007/bf03346819
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting hyperparathyroidism with thyrotoxicosis

Abstract: The coexistence of hyperparathyroidism complicating thyrotoxicosis is quite rare. We report the case of one patient who presented with thyrotoxicosis, (total thyroxine of 15.1 micrograms/dl (5-13), free thyroxine index of 18 (4-15) and triiodothyronine by RIA of 305 ng/dl (70-230) and asymptomatic hypercalcemia of 15 mg/dl (8.5-10.6), who was also initially noted to have an elevated (C-terminal) serum immunoreactive parathyroid hormone (iPTH) level of 8,800 pg/ml (50-340). With propylthiouracil and propranolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…It has also been suggested that relative decrease in calcitonin in thyrotoxicosis stimulates parathyroid hormone production [11]. Some reports have therefore recommended observation of the serum levels of calcium and PTH until the patient becomes euthyroid due to antithyroid therapy [11,27]. We were unable to have an observation period since rapid growth of the thyroid nodule in our patient necessitated immediate surgical treatment.…”
Section: Discussionmentioning
confidence: 89%
“…It has also been suggested that relative decrease in calcitonin in thyrotoxicosis stimulates parathyroid hormone production [11]. Some reports have therefore recommended observation of the serum levels of calcium and PTH until the patient becomes euthyroid due to antithyroid therapy [11,27]. We were unable to have an observation period since rapid growth of the thyroid nodule in our patient necessitated immediate surgical treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The coexistence of hyperparathyroidism and thyrotoxicosis was considered to be rare in the past (6,14). However, Abboud et al reported the coexistence of thyrotoxicosis in 13 of 96 (13.5%) patients admitted for surgery for hyperparathyroidism (6).…”
Section: Discussionmentioning
confidence: 99%
“…A hipercalcemia associada à tireotoxicose pode ocorrer em 2-5% destes pacientes e seria decorrente principalmente de um aumento da reabsorção óssea (52). Na maioria dos casos, a hipercalcemia é assintomática e normaliza com o eutiroidismo (52,53).…”
Section: Tireotoxicoseunclassified
“…Na maioria dos casos, a hipercalcemia é assintomática e normaliza com o eutiroidismo (52,53). No entanto, associação de HPT primário com tireotoxicose pode ocorrer, embora pouco freqüente (<1% casos) (54).…”
Section: Tireotoxicoseunclassified